When is Sirt1 activity bad for dying neurons? - Tang, Bor Luen; Ng, Fanny (Frontiers in Cellular Neuroscience, 2013)
Sirt1, the class III histone deacetylase, is generally associated with increased life span and with a pro-survival effect in neurons stressed by pathological factors. Recent work, however, suggests that Sirt1 silencing could also promote neuronal survival. A possible reason suggested is Sirt1 silencing enhanced expression of both IGF-1 and IGF-1 receptor, signaling from which promotes survival. This work adds to the small but steady stream of findings that are diametrically opposite to the overwhelmingly large amount of evidence supporting a beneficial effect of sustaining or enhancing Sirt1 activity in neuronal injuries and diseases. We attempt to reconcile this discrepancy below by noting evidence that elevated Sirt1 levels and/or activity may not help, and could even adversely exacerbates demise, during events of acute neuronal damage or death. However, sustained Sirt1 activation will be beneficial in situations of chronic and long-term sub-lethal stresses, and the status of IGF-1 signaling may influence Sirt1 action in a context dependent manner.